Effects of Deuterium Isotopes on Pt(II) Complexes and Their Impact on Organic NIR Emitters - Wang, Sheng‐Fu; Zhou, Dong‐Ying; Kuo, Kai‐Hua; Wang, Chih‐Hsing; Hung, Chieh‐Ming; Yan, Jie; Liao, Liang‐Sheng; Hung, Wen‐Yi; Chi, Yun; Chou, Pi‐Tai (Angewandte Chemie International Edition, 2024)
Insight into effect of deuterium isotopes on organic near‐IR (NIR) emitters was explored by the use of self‐assembled Pt(II) complexes H‐3‐f and HPh‐3‐f, and their deuterated analogues D‐3‐f and DPh‐3‐f, respectively (Scheme 2). In vacuum deposited thin film, albeit having nearly identical emission spectral feature maximized at ~810 nm, H‐3‐f and D‐3‐f exhibit remarkable difference in photoluminescence quantum yield (PLQY) of 29 % and 50 %, respectively. Distinction in PLQY is also observed for HPh‐3‐f (800 nm, 50 %) and DPh‐3‐f (798 nm, 67 %). We then elucidated the theoretical differences in the impact on near‐infrared (NIR) luminescence between Pt(II) complexes and organic small molecules upon deuteration. The results establish a general guideline for the deuteration on NIR emission efficiency. From a perspective of practical application, NIR OLEDs based on D‐3‐f and DPh‐3‐f emitters attain EQEmax of 15.5 % (radiance 31,287 mW Sr−1 m−2) and 16.6 % (radiance of 32,279 mW Sr−1 m−2) at 764 nm and 796 nm, respectively, both of which set new records for NIR OLEDs of >750 nm. We have developed general guidelines for the effect of deuterium isotopes on the NIR emission efficiency of Pt(II) complexes and common organic NIR emitters. Also, in this study the NIR OLED based on deuterated Pt(II) complex DPh‐3‐f emitter attains 796 nm electroluminescence with EQEmax of 16.6 % and radiance of 32,279 mW Sr−1 m−2, which sets new records for NIR OLEDs of >750 nm.